2020
DOI: 10.1097/fjc.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Higenamine Improves Cardiac and Renal Fibrosis in Rats With Cardiorenal Syndrome via ASK1 Signaling Pathway

Abstract: The pathogenesis of cardiorenal syndrome (CRS) is very complex, and currently there is no effective treatment for CRS. Higenamine (HI) has been shown to improve cardiac function in rats with heart failure. However, the role of higenamine in CRS remains unknown. Here, in vitro, higenamine treatment markedly reduced neonatal rat cardiac fibroblast collagen synthesis and inhibited neonatal rat cardiac myocyte hypertrophy. In our study, a rat model of type 2 CRS was induced by left anterior descending coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For example, Deng et al presented that higenamine may target the ASK1/MAPK (ERK and P38)/NF- κ B signaling pathway to improve cardiorenal function and alleviate cardiac and renal fibrosis in CRS rats. In addition, higenamine was also found to significantly inhibit the protein expression of mitogen-activated protein kinase (MAPK) (ERK and P38)/NF- κ B pathway in CRS rats and then to protect rat cardiomyocytes [ 30 ]. Cai et al discovered that melatonin and exendin-4 treatment exerted protective effects on the heart of CRS rats through the TNF- α /NF- κ B/MMP-2/MMP-9/IL-1 β pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Deng et al presented that higenamine may target the ASK1/MAPK (ERK and P38)/NF- κ B signaling pathway to improve cardiorenal function and alleviate cardiac and renal fibrosis in CRS rats. In addition, higenamine was also found to significantly inhibit the protein expression of mitogen-activated protein kinase (MAPK) (ERK and P38)/NF- κ B pathway in CRS rats and then to protect rat cardiomyocytes [ 30 ]. Cai et al discovered that melatonin and exendin-4 treatment exerted protective effects on the heart of CRS rats through the TNF- α /NF- κ B/MMP-2/MMP-9/IL-1 β pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that higenamine improves cardiomyocyte fibrosis and dysfunction by inhibiting TGF-β1/Smad signaling and cardiac fibroblasts activation. Deng et al (2020) , also found that higenamine dramatically inhibits the collagen synthesis of NRCF and inhibits the hypertrophy of neonatal rat cardiomyocytes. It mainly mediates ASK1 pathways to relieve cell fibrosis ( Table 3 ).…”
Section: Effects Of Higenamine On Heart Disease In Vitromentioning
confidence: 89%
“…Currently, higenamine is considered to be effective in the treatment of CRS. A study from Deng ( Deng et al, 2020 ) revealed that compared with type 2 CRS rats, rats treated with higenamine (0.5–4.5 mg kg −1 ) showed significantly increased LV ejection fraction (LVEF%) and left ventricular fraction shortening (LVFS%), decreased LV end systolic volume (LVESV), LV posterior wall thickness LVPW, Cardiac weight index (CWI) and kidney weight index (KWI). In addition, higenamine markedly decreased serum creatinine (Scr), blood urea nitrogen (BUN), indole sulfate (IS), and 24-h urine protein level as well as memorably diminished cardiac and renal fibrosis in CRS rats, accompanied with the reduced protein level of α-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and collagen I.…”
Section: Effects Of Higenamine On Heart Disease In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The p38 MAPK is stimulated and activated by cytokines and environmental stress and belongs to stress-activated protein kinases, which are involved in regulating cell proliferation, differentiation, and apoptosis [ 26 ]. ASK1, a member of the MAP3K family, is ROS-sensitive and is a key gene in oxidative stress-mediated apoptosis [ 27 ]. After oxidative stress, the Thr 845 site of ASK1 is phosphorylated and then activated, and activated ASK1 can phosphorylate downstream MKK4 and MKK7, which can phosphorylate downstream MKK3 and MKK6, which activate p38 by phosphorylating Thr180 and Tyr182 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%